Body Size and Symmetry Properties of Termite Soldiers Under Two Intraspecific Competition Scenarios - Aguilera-Olivares, Daniel; Torres-Guzmán, Bárbara; Arab, Alberto; Flores-Prado, Luis; Niemeyer, Hermann M. (Frontiers in Ecology and Evolution, 2022)
Single-piece nesting termites live and forage in the same piece of wood throughout their life, which limit their colony size. In certain species, more than one colony thrive in a given piece of wood (multicolonial substrate) and intraspecific competition become important in this limited resource, as has been reported in Zootermopsis nevadensis (Hagen, 1858) and Neotermes chilensis (Blattodea: Kalotermitidae) (Blanchard, 1851). The effects of such competition have been described mainly at population and colony levels rather than at the individual level. In eusocial insects such as termites, intraspecific competition constitutes a stress factor imposed to a colony as a whole and should also cause developmental instability in soldiers produced under such conditions. Investment in the production of soldiers involves a trade-off between colony maintenance costs and defense benefits. Hence, we hypothesize that body size and fluctuating asymmetry, two indicators of developmental instability, will increase when two or more colonies of N. chilensis share a piece of wood (high intraspecific competition scenario). Our results showed that soldiers developing in multicolonial substrates were indeed larger and more asymmetric than soldiers developing in unicolonial substrates. The large body size in a soldier could improve its chance to win a physical contest with a non-nestmate opponent; thus, despite the high cost to produce large soldiers in small colonies, larger soldier production could be an adaptative strategy to avoid being outcompeted. However, the effects of deviations from perfect symmetry on soldier performance are not clear.